Expeditions in Selected ›Word Landscapes‹ of Middle and Eastern Europe (KULT_online, 2010)
Editors Magdalena Marszałek and Sylvia Sasse as well as the other authors of the anthology Geopoetiken (Geopoetics) successfully locate and distinguish 'Geopoetik' theoretically in the field of existing concepts for analysing space in literature/art, and show the concept's productivity and interdisciplinary operability for textual analysis. Eleven very precise articles, most of them analysing texts from south- and mideastern European literatures, depict and reflect on, on the one hand, the medial production of geography and on the other hand the relationship between creativity and the geographical space where an artefact is produced.